Programmable logic devices in sensor networks: a survey - Iacono, Lucas (2011)
This paper presents a survey about the use of reconfigurable hardware technologies in sensor networks, considering proposals published in two of the leading conferences of Programmable Logic Devices: FPL and SPL. These proposals cover different applications such as wireless communications, different networks topics and sensors. Some of the papers considered in this survey are directly related with WSN, such as reconfigurable nodes or lowpower hardware platforms intended for sensor networks. Other papers are not directly related to WSN, but they present results and concepts that may be of interest in the field of the WSNs.